Immune Responses to Mycobacterium tuberculosis Infection in the Liver of Diabetic Mice - Ali Badaoui; Kayvan Sasaninia; Aishvaryaa Shree Mohan; Abrianna Beever; Nala Kachour; Anmol Raien; Afsal Kolloli; Ranjeet Kumar; Santhamani Ramasamy; Selvakumar Subbian; Vishwanath Venketaraman (Biomedicines, 2024)
Individuals with uncontrolled diabetes are highly susceptible to tuberculosis (TB) caused by Mycobacterium tuberculosis (M. tb) infection. Novel treatments for TB are needed to address the increased antibiotic resistance and hepatoxicity. Previous studies showed that the administration of liposomal glutathione (L-GSH) can mitigate oxidative stress, bolster a granulomatous response, and diminish the M. tb burden in the lungs of M. tb-infected mice. Nonetheless, the impact of combining L-GSH with conventional TB treatment (RIF) on the cytokine levels and granuloma formation in the livers of diabetic mice remains unexplored. In this study, we evaluated hepatic cytokine profiles, GSH, and tissue pathologies in untreated and L-GSH, RIF, and L-GSH+RIF treated diabetic (db/db) M. tb-infected mice. Our results indicate that treatment of M. tb-infected db/db mice with L-GSH+RIF caused modulation in the levels of pro-inflammatory cytokines and GSH in the liver and mitigation in the granuloma size in hepatic tissue. Supplementation with L-GSH+RIF led to a decrease in the M. tb burden by mitigating oxidative stress, promoting the production of pro-inflammatory cytokines, and restoring the cytokine balance. These findings highlight the potential of L-GSH+RIF combination therapy for addressing active EPTB, offering valuable insights into innovative treatments for M. tb infections.